Deterministic approach Available Transfer Capability (ATC) calculation methods - Khairuddin, Azhar; Khalifa, Othman O.; Alhammi, Abdelwahab I.; Larik, Raja Masood (2016)
With the new strategy of deregulation electrical power systems, Available Transfer Capability (ATC) is significant indicator. This paper debate for deterministic methods to compute ATC. Concepts and calculation approaches of Optimal Power Flow (OPF), Continuation Power Flow (CPF) and Power Transfer Distribution Factors (PTDF) has been presented. Cons and prons of each with simulated results are presented using IEEE 30 -bus test systems without any contingences proposed, the results shows efficient results with high performance accuracy